Different Effects of Insulin-Like Growth Factor-1 and Insulin-Like Growth Factor-2 on Myogenic Differentiation of Human Mesenchymal Stem Cells. (14th December 2017) - Aboalola, Doaa; Han, Victor K. M.
Abstract : Insulin-like growth factors (IGFs) are critical components of the stem cell niche, as they regulate proliferation and differentiation of stem cells into different lineages, including skeletal muscle. We have previously reported that insulin-like growth factor binding protein-6 (IGFBP-6), which has high affinity for IGF-2, alters the differentiation process of placental mesenchymal stem cells (PMSCs) into skeletal muscle. In this study, we determined the roles of IGF-1 and IGF-2 and their interactions with IGFBP-6. We showed that IGF-1 increased IGFBP-6 levels within 24 hours but decreased after 3 days, while IGF-2 maintained higher levels of IGFBP-6 throughout myogenesis. IGF-1 increased IGFBP-6 in the early phase as a requirement for muscle commitment. In contrast, IGF-2 enhanced muscle differentiation as shown by the expression of muscle differentiation markers MyoD, MyoG, and MHC. IGF-1 and IGF-2 had different effects on muscle differentiation with IGF-1 promoting early commitment to muscle and IGF-2 promoting complete muscle differentiation. We also showed that PMSCs acquired increasing capacity to synthesize IGF-2 during muscle differentiation, and the capacity increased as the differentiation progressed suggesting an autocrine and/or paracrine effect. Additionally, we demonstrated that IGFBP-6 could enhance the muscle differentiation process in the absence of IGF-2.